Effect of Bad Debts (NPL), Market Capitalization, Operation Cost, Capital Adequacy, Cash Reserve on the Profitability of Nepalese Commercial Banks - Bhandari, Nelka (Nepalese Journal of Finance, 2024)
This study examines the effect of bad debts, market capitalization, operation cost, capital adequacy ratio and cash reserve ratio on the profitability of Nepalese commercial banks. Return on asset and return on equity are selected as the dependent variables. Similarly, non-performing loan, market capitalization, operation cost, capital adequacy ratio, cash reserve ratio and leverage are selected as the independent variables. This study is based on secondary data of 15 commercial banks with 120 observations for the study period from 2014/15 to 2021/22. The data were collected from Banking and Financial Statistics published by Nepal Rastra Bank, annual reports of the selected commercial banks and reports published by Ministry of Finance. The correlation coefficients and regression models are estimated to test the significance and importance of bad debts (NPL), market capitalization, operation cost, capital adequacy ratio and cash reserve ratio on the profitability of Nepalese commercial banks. The study showed that non-performing loan has a negative impact on return on assets and return on equity. It indicates that increase in non-performing leads to decrease in return on assets and return on equity. In addition, operation cost has a negative impact on return on assets. It means that increase in operation cost leads to decrease in return on assets. Likewise, capital adequacy ratio has a positive impact on return on assets. It indicates that increase in capital adequacy ratio leads to increase in return on assets. Moreover, leverage ratio has a negative impact on return on assets. It indicates that increase in leverage leads to decrease in return in assets of Nepalese commercial banks. Similarly, market capitalization has a positive impact on return on equity. It indicates that increase in market capitalization leads to increase in return on equity. In addition, operation cost has a negative relationship with return on assets and return on equity. It means that increase in operation cost leads to decrease in return on assets and return on equity.